A PORTRAIT OF THE SAKINAH FAMILY IN MANUSCRIPT TEXTS BY WOMEN SCHOLARS FROM THE PESANTREN - Samsul Arifin; Ummi Khairiyah; Minhaji Minhaji (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2019)
Abstract. The formation of the personality characteristics of a married couple is very important and decisive inthinking and acting in building a sakinah household. Sakinah will appear in the calmness of the heart and the clarity of their minds. The scholars, including women scholars from the pesantren have written about it. The purpose of this paper is to uncover and describe the ideal quality of the personality of a married couple in the eyes of women scholars from the pesantren. This article is interesting, because so far many books on household written by male scholars, not female scholars, so it tends to be paternalistic. This paper is useful for the development of Marriage Counseling science based on local pesantren wisdom. The focus of this paper is the portrait of the quality of the personality of a married couple in reaching a sakinah family in the book Zadu Az-Zaujayn (a reinterpretation of the book of Uqud al-Lujjayn ) by Ibu Nyai Zainiyah As'ad, Pondok Pesantren Salafiyah Syafi'iyah Sukorejo Situbondo from the perspective of marriage counseling. This research method uses Gadamer's hermeneutic approach. The results showed, married couples should have the quality of personality that has knowledge (about some rights and obligations, fiqh of women, and the ability to educate children), gracefully when bitter experiences (sabar), affection, acceptance of life as is (ridha and ikhlas), and create a good impression of their partner (self presentation). The focus of marriage counseling adhered to by the pesantren is directed at the improvement and development of the quality of the personality of a married couple rather than the problems in the marriage itself. If a married couple has a good personality then problems in a marriage can be solved by themselves. That personality will radiate in thinking and acting in everyday life to create a sakinah family.Abstrak. Pembentukan karakteristik kepribadian pasangan menikah sangat penting dan menentukan dalam berpikir dan bertindak dalam membangun rumah tangga sakinah. Sakinah akan muncul dalam ketenangan hati dan kejernihan pikiran mereka. Para cendekiawan, termasuk cendekiawan perempuan dari pesantren telah menulis tentang itu. Tujuan dari makalah ini adalah untuk mengungkap dan menggambarkan kualitas ideal kepribadian pasangan yang sudah menikah di mata ulama perempuan dari pesantren. Artikel ini menarik, karena selama ini banyak buku tentang rumah tangga yang ditulis oleh sarjana laki-laki, bukan sarjana perempuan, sehingga cenderung paternalistik. Makalah ini bermanfaat untuk pengembangan ilmu Konseling Perkawinan berdasarkan kearifan lokal pesantren. Fokus dari makalah ini adalah potret kualitas kepribadian pasangan yang sudah menikah dalam mencapai keluarga sakinah dalam buku Zadu Az-Zaujayn (reinterpretasi buku Uqud al-Lujjayn) oleh Ibu Nyai Zainiyah As'ad, Pondok Pesantren Salafiyah Syafi'iyah Sukorejo Situbondo dari perspektif konseling perkawinan. Metode penelitian ini menggunakan pendekatan hermeneutik Gadamer. Hasil penelitian menunjukkan, pasangan suami istri harus memiliki kualitas kepribadian yang memiliki pengetahuan (tentang beberapa hak dan kewajiban, fiqh perempuan, dan kemampuan untuk mendidik anak), anggun ketika pengalaman pahit (sabar), kasih sayang, penerimaan hidup apa adanya ( ridha dan ikhlas), dan menciptakan kesan yang baik tentang pasangan mereka (presentasi diri). Fokus konseling perkawinan yang dianut oleh pesantren diarahkan pada peningkatan dan pengembangan kualitas kepribadian pasangan menikah daripada masalah dalam pernikahan itu sendiri. Jika pasangan menikah memiliki kepribadian yang baik maka masalah dalam perkawinan dapat diselesaikan sendiri. Kepribadian itu akan terpancar dalam pemikiran dan tindakan dalam kehidupan sehari-hari untuk menciptakan keluarga sakinah.